2011
DOI: 10.1111/j.1528-1167.2011.03063.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of phenotypes in female patients with epilepsy due to protocadherin 19 mutations

Abstract: SUMMARYPurpose: To describe clinical and neuropsychological features of six consecutive sporadic girls with protocadherin 19 (PCDH19) mutations. Methods: Following recent descriptions of PCDH19 mutation in girls with epilepsy, we sequenced this gene in patients with infantile or early childhood seizures onset, either focal or generalized, without an obvious etiology. Key Findings: Mean age at the time of the study was 13.5 ± 11 years. Mean age at seizure onset was 15.5 ± 11 months (range 9-38). All patients ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 12 publications
3
74
0
3
Order By: Relevance
“…In both of our cases, fever determined a worsening of seizures, as was also previously reported [8,21,27,29,30]. Seizure recurrence might be in clusters, as reported for other genetic epileptic conditions such as epilepsy due to PCDH19 mutation [33], and a differential diagnosis should be considered in those cases.…”
Section: Discussionsupporting
confidence: 52%
“…In both of our cases, fever determined a worsening of seizures, as was also previously reported [8,21,27,29,30]. Seizure recurrence might be in clusters, as reported for other genetic epileptic conditions such as epilepsy due to PCDH19 mutation [33], and a differential diagnosis should be considered in those cases.…”
Section: Discussionsupporting
confidence: 52%
“…In female patients, seizure frequency often diminishes around puberty [3, 5, 11, 28–30], possibly due to hormonal changes [30]. Our 13-year old patient has been seizure free since the age of 10 years old; our 10-year-old patient only has one cluster of seizures per year.…”
Section: Discussionmentioning
confidence: 90%
“…Further studies have shown that over 10% of cohorts of girls with onset of seizures under 5 years of age have PCDH19 mutations; many are de novo mutations and therefore do not have the characteristic family history seen in EFMR (21)(22)(23). Girls with normal intellect or intellectual disability who present with clusters of brief febrile seizures in infancy should be considered for PCDH19 testing.…”
Section: Pcdh19 Encoding Protocadherin 19mentioning
confidence: 99%